Fundamentalisme Islam: Sejarah dan Gerakan - - Yusdani (Unisia, 2002)
The fundamentalism of Islam emerges because of two factors- either external factor or internal factor. The external factor that causes appearing of the fundamentalism of Islam covering the fact that Muslim world faces the challenge of modernism, secularism and westernize tend to marginalize the religion (Islam) position in respective Muslim society. Whereas the internal factor includes the phenomena of religious particularly the moral decadence that happens in Muslim society. Besides, according to some researcher's analyse regarding the emerging of the fundamentalism of Islam indicates that muslim can not answer the challenge of modernity creatively and they interpret the basic doctrine of Islam rigidly and textually that not in accordance with recent situation. In other word, they do not perceive Islam by using contextual interpretation.